Given equation is
"\\frac{dN}{dt} = \\tau (N - \\frac{N^2}{q})"
Integrating the above equation
"\\frac{dN}{(\\frac{N^2}{q} - N)} = - \\tau dt"
Integrating it,
"\\int \\frac{dN}{(\\frac{N^2}{q} - N)} = - \\int\\tau dt"
Solving it we get,
"ln|1-\\frac{q}{N}| = -\\tau t + C"
Putting boundary equations, N(0) = N0
Then we get
"ln|1-\\frac{q}{N_0}| = C"
Hence, we can say that
"ln|1-\\frac{q}{N}| = -\\tau t + ln|1-\\frac{q}{N_0}|"
It can be written as
"ln|\\frac{N(N_0-q)}{N_0(N-q) }| = \\tau t"
Comments
Leave a comment